Eneolithic menhirs of Laconi (central Sardinia, Italy): from provenance to technological properties. (February 2016) - Serra, Marco; Mameli, Valentina; Cannas, Carla
Abstract: A multi-technique approach was carried out to investigate the provenance and technological properties of 34 anthropomorphic menhirs from Laconi (central Sardinia, Italy) dated back to the local Copper Age (III millennium BC). After visual inspection, geological materials coming from local ignimbritic outcrops were characterized by elemental and mineralogical analyses: portable X-Ray Fluorescence (pXRF), Inductively Coupled Plasma-Optical Emission Spectrometry (ICP-OES), Inductively Coupled Plasma-Mass Spectrometry (ICP-MS) and Powder X-Ray Diffraction (PXRD). Conversely, the menhirs were studied only by visual examination and non-destructive pXRF measurements. By means of a comparison between pXRF data collected on the menhirs and the lithological outcrops, it was possible to assign the prehistoric artifacts of Laconi to local geo-sources, taking into account geochemical intra- and inter-source variabilities. pXRF was demonstrated to be a useful tool for provenance studies while mineralogical analysis resulted fundamental for the technological aspects. The latter technique pointed out the main use of hardstones, probably owing to the durability they give to the menhirs. To the best of our knowledge, this is the first archaeometric study on Sardinian menhirs and one of the few recently developed on European megaliths. Graphical abstract: Highlights: Provenance study on Sardinian menhirs by non-destructive pXRF Raw material selection on the basis of durability Connection between durability and the symbolic meaning of the menhir bas-reliefs Red pigments for the decoration of menhirs